Y1 receptor ligand-based nanomicelle as a novel nanoprobe for glioma-targeted imaging and therapy. Issue 13 (15th March 2018) - Li, Juan; Du, Yang; Jiang, Zhenqi; Tian, Yuchen; Qiu, Nianxiang; Wang, Yinjie; lqbal, Muhammad Zubair; Hu, Menying; Zou, Ruifen; Luo, Lijia; Du, Shiyu; Tian, Jie; et al.
Abstract : Y1 receptor ligand AP-NPY facilitates circumvention of the blood brain barrier by nanomicelles specifically targeting glioma, improving therapeutic efficacy and prolonging survival. Abstract : Due to the molecular and cellular heterogeneity of glioma, discovery of novel targeted sites and ligands for glioma imaging and therapy remains challenging. Neuropeptide Y (NPY) Y1 receptors (Y1 Rs) are highly over expressed in various brain tumors including glioma, and can serve as potential targeting sites for glioma imaging and therapy. Here, we show by in vivo fluorescent imaging that a highly selective Y1 R ligand, [Asn 6, Pro 34 ] NPY (AP-NPY), facilitated circumvention of the blood brain barrier (BBB) by nanomicelles specifically targeting glioma. Modification with AP-NPY stabilized doxorubicin-loaded nanomicelles in the normal physiological state and promoted drug release in the acidic tumor microenvironment. Furthermore, targeted delivery of AP-NPY nanomicelles improved the therapeutic efficacy of doxorubicin for glioma, producing a prolonged survival rate. These results suggest that Y1 R is a novel targeted receptor, and its selective ligand AP-NPY improves BBB permeability and glioma targeting. Our study paves the way for developing a novel delivery system for diagnosis and treatment of glioma in which Y1 Rs are over expressed.